Pengaruh Pelatihan Terhadap Pengambilan Keputusan Skrining Kanker Serviks Berdasarkan The Precaution Adoption Process Model - Vitniawati, Vina; Hermayanti, Yanti; Kurniawan, Titis (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
Decision making for taking screening is an important component in preventing cervical cancer, but still many women who have not yet done it due to a lack of knowledge and decision-making ability.  Development of intervention tailored to the stages of decision-making based on the Precaution  Adoption  Process  Model,  such as training,  is able to improve decision-making ability to do the screening. This study aimed to determine the differences in the effect of training on decision-making for cervical cancer screening based on PAPM in the UPT Griya Antapani Health Center Bandung. This quasi-experimental study with two group pre-test post-test design involved  84  women aged  30-49  years who were chosen by purposive and proportional cluster sampling from two villages divided into  42  respondents each. Group  A received training with PowerPoint media,  leaflets,  videos, and WhatsApp while group  B received training with PowerPoint media, leaflets, and videos. The data of decision-making was collected using the  Precaution Adoption Process Model checklist:  before,  after training, and  15  days after training then analyzed using  Friedman test and  Mann  Whitney test.  The results showed that there were differences in decision-making in each group before and after training with p <0.001 but Mann Whitney test showed that there was no difference in decision-making between groups after training (p = 1,000 and p = 0.316). This depicted that any method and media can be used to change decision-making. Providing training and counseling is needed according to the stages of decision-making taking into account the factors that influence it.  Keywords: Cervical Cancer, Decision-making, Screening, the Precaution Adoption Process Model